IN THE SHADOW OF COVID-19: THE RELATIONSHIP BETWEEN SLEEP AND EMOTION IN SCHOOL-AGED CHILDREN - Mustafa Tunca; Meltem Kürtüncü (Sabuncuoglu Serefeddin Health Sciences, 2026)
This descriptive and analytical study was conducted to determine the interplay between sleep patterns and emotional states of school-age children during the global pandemic. The sample of this descriptive and cross-sectional study consisted of 407 volunteer parents whose children were enrolled in a primary school in a province in the Western Black Sea Region. Data were collected online using the “Demographic Information Form,” the “Children's Sleep and Sleep Habits Questionnaire,” and the “Strengths and Difficulties Questionnaire.” The mean score for the Strengths and Difficulties Questionnaire was 16.69±5.77, while the mean score for the Sleep Habits Questionnaire was 57.31±10.88. Regarding the age variable, it was found that the 9-year-old group had significantly higher scores on both scales (p<0.0001). Children with low academic achievement demonstrated higher scores compared to those with moderate or high achievement levels (p < 0.05). Furthermore, a positive correlation was observed between increased emotional difficulties and heightened sleep-related problems (F=421.191; p < 0.05). It was concluded that the pandemic period adversely affected children's sleep hygiene and emotional well-being. These findings highlight the importance of implementing psychosocial protective measures and supportive nursing interventions during crisis periods to enhance children's health outcomes.